Revelation through violence? Jesus in the Temple in John 2:13–22 - Myers, Alicia D. (Review and expositor, 2023)
John’s version of Jesus’s temple entrance is remarkable for its depiction of Jesus wielding a whip and driving out animals and people from the precincts. Focusing on the violence of Jesus’s “righteous anger,” some interpreters have used John 2:13–22 to justify violence in God’s name throughout history. Others push back against such readings by mitigating or ignoring the violence of Jesus’s actions. This article seeks to find a middle ground by focusing on ancient understandings of what happens when holiness is profaned. Using 2 Maccabees as a comparison, I argue John 2:13–22 presents Jesus’s arrival in the temple as a clash caused by holiness breaking out. This presentation emphasizes Jesus’s identity as God’s glory made flesh and plays into ancient audience expectations in 2:13–17. In 2:18–22, however, Jesus undercuts these assumptions by predicting his own death and resurrection. Rather than endorsing violence, then, John 2:13–22 is better understood as a type of bait and switch, in which the narrative emphasizes Jesus’s identity, the problem he faces in the world, and the surprising way God responds. Instead of spreading violence, Jesus receives it upon his own body, thus revealing God’s inviolability that results in life for those who will receive it.